Butler and the agency capacity of political subjects: the debate with Fraser and the influences of Foucault and Derrida - Cunha Blanco, Daniela (2024)
Butler and the agency capacity of political subjects: the debate with Fraser and the influences of Foucault and Derrida   Abstract: The article intends to present Nancy Fraser's main criticism of Judith Butler's thought, around the issue of the agency capacity of political subjects, taking sides in defending Butler's thought. It is argued that Fraser fails to understand how Butler conceives an idea of power based on Michel Foucault, whose very functioning demands another understanding not only of what a subject is, but also of what we can call political action. Thus showing how Butler constructs a gender theory based on the concept of performativity and with the influences of Foucault and Derrida, we argue that the author conceives an idea of radical intersectionality, from which power becomes diffuse and positive and the political agency is understood within the flaws and fissures operated by the functioning of power itself.